PENGARUH HAFALAN AL-QUR’AN TERHADAP PRESTASI AKADEMIK MAHASISWA FAI UNIVERSITAS AHMAD DAHLAN YOGYAKARTA - Suwandi Suwandi; Rofiul Wahyudi (Universitas Muhammadiyah Ponorogo, 2020)
This study aims at determining the effect of reciting the Koran to the academic achievements of the students of the Faculty of Islam, Universitas Ahmad Dahlan Yogyakarta. The research method applied in this study was descriptive quantitative approach. The population is all students of the Faculty of Islam while the sample selection is based on the non-probability sampling method, especially the purposive sampling method, which amounts to 62 out of 70 respondents who are memorizers of the Koran. The instrument used in this study was a questionnaire containing closed questions. The data analysis technique used descriptive statistical analysis with PSPP 1.2. The findings showed that there was a positive and significant influence of memorizing the Koran to the students' academic achievement. The statistical test results showed a significant value of 0.000, which meant a positive and significant effect